Balancing burdens of infection control: Norwegian district medical officers' ethical challenges during the COVID-19 pandemic - Linn Brøderud; Reidar Pedersen; Morten Magelssen (BMC, 2023)
Abstract Background In several countries, district medical officers (DMOs) are public health experts with duties including infection control measures. The Norwegian DMOs have been key actors in the local handling of the COVID-19 pandemic. Methods The aim of the study was to explore the ethical challenges experienced by Norwegian DMOs during the COVID-19 pandemic, and how the DMOs have handled these challenges. 15 in-depth individual research interviews were performed and analyzed with a manifest approach. Results Norwegian DMOs have had to handle a large range of significant ethical problems during the COVID-19 pandemic. Often, a common denominator has been the need to balance burdens of the contagion control measures for different individuals and groups. In another large set of issues, the challenge was to achieve a balance between safety understood as effective contagion prevention on the one hand, and freedom, autonomy and quality of life for the same individuals on the other. Conclusions The DMOs have a central role in the municipality's handling of the pandemic, and they wield significant influence. Thus, there is a need for support in decision-making, both from national authorities and regulations, and from discussions with colleagues.